Intrafamilial Phenotypic Variability in the C9orf72 Gene Expansion: 2 Case Studies - Foxe, David; Elan, Elle; Burrell, James R.; Leslie, Felicity V. C.; Devenney, Emma; Kwok, John B.; Halliday, Glenda M.; Hodges, John R.; Piguet, Olivier (Frontiers in Psychology, 2018)
The C9orf72 genetic mutation is the most common cause of familial frontotemporal dementia (FTD) and motor neuron disease (MND). Previous family studies suggest that while some common clinical features may distinguish gene carriers from sporadic patients, the clinical symptoms, age of onset and disease progression vary considerably in affected patients. Here, we report two individuals with a C9orf72 repeat expansion from two generations of the same family with markedly different clinical presentation and disease progression: one who developed motor neuron and behavioural symptoms at 46 years of age and died three years later with confirmed TDP-43 pathology and motor neuron disease; and a second who developed cognitive and mild behavioural symptoms at age 75 years and at age 83 remains alive with only slow deterioration.